Physiological pharmacology. a comprehensive treatise - Root, Walter S. (Walter Stanton), 1902-1972; Hofmann, Frederick G. (Academic Press, 1967)
Physiological Pharmacology: A Comprehensive Treatise, Volume IV: The Nervous System - Part D: Autonomic Nervous System Drugs focuses on the effects of drugs on the nervous system, including how adrenergic drugs affect the heart and systemic circulation, metabolism, and adrenergic compounds. The selection first offers information on the effects of adrenergic drugs on the heart and systemic circulation. Topics include actions of adrenergic drugs, possible drug actions on the heart, epinephrine and arterenol, and other sympathomimetic drugs. The book then examines the effects of adrenergic compo.